The role of the kynurenine pathway in cardiovascular disease - Yang, Yuehang; Liu, Xing; Liu, Xinyi; Xie, Chiyang; Shi, Jiawei (Frontiers in Cardiovascular Medicine, 2024)
The kynurenine pathway (KP) serves as the primary route for tryptophan metabolism in most mammalian organisms, with its downstream metabolites actively involved in various physiological and pathological processes. Indoleamine 2,3-dioxygenase (IDO) and tryptophan 2,3-dioxygenase (TDO) serve as the initial and pivotal enzymes of the KP, with IDO playing important and intricate roles in cardiovascular diseases.Multiple metabolites of KP have been observed to exhibit elevated concentrations in plasma across various cardiovascular diseases, such as atherosclerosis, hypertension, and acute myocardial infarction. Multiple studies have indicated that kynurenine (KYN) may serve as a potential biomarker for several adverse cardiovascular events. Furthermore, Kynurenine and its downstream metabolites have complex roles in inflammation, exhibiting both inhibitory and stimulatory effects on inflammatory responses under different conditions. In atherosclerosis, upregulation of IDO stimulates KYN production, mediating aromatic hydrocarbon receptor (AhR)-induced exacerbation of vascular inflammation and promotion of foam cell formation. Conversely, in arterial calcification, this mediation alleviates osteogenic differentiation of vascular smooth muscle cells. Additionally, in cardiac remodeling, KYN-mediated AhR activation exacerbates pathological left ventricular hypertrophy and fibrosis. Interventions targeting components of the KP, such as IDO inhibitors, 3-hydroxyanthranilic acid, and anthranilic acid, demonstrate cardiovascular protective effects. This review outlines the mechanistic roles of KP in coronary atherosclerosis, arterial calcification, and myocardial diseases, highlighting the potential diagnostic, prognostic, and therapeutic value of KP in cardiovascular diseases, thus providing novel insights for the development and application of related drugs in future research.